Destroy all neighbors [videorecording (DVD)] - Pieper, Charles; Logan, Jared; Rodrigues, Jonah Ray; Winter, Alex, 1965-; Deol, Kiran; Heller, Randee, 1947-; Daly, Jon (Comedian); Lennon, Thomas, 1970- (Shudder, 2024)
A struggling prog-rock musician finds himself in a living nightmare when he accidentally kills the neighbor from hell.